Radiotherapy resistance: identifying universal biomarkers for various human cancers - Larionova, Irina V.; Rakina, Militsa; Ivanyuk, Elena E.; Trushchuk, Yulia; Chernyshova, Alena; Denisov, Evgeny V. (Journal of cancer research and clinical oncology)
Radiotherapy (RT) is considered as a standard in the treatment of most solid cancers, including glioblastoma, lung, breast, rectal, prostate, colorectal, cervical, esophageal, and head and neck cancers. The main challenge in RT is tumor cell radioresistance associated with a high risk of locoregional relapse and distant metastasis. Despite significant progress in understanding mechanisms of radioresistance, its prediction and overcoming remain unresolved. This review presents the state-of-the-art for the potential universal biomarkers correlated to the radioresistance and poor outcome in different cancers. We describe radioresistance biomarkers functionally attributed to DNA repair, signal transduction, hypoxia, and angiogenesis. We also focus on high throughput genetic and proteomic studies, which revealed a set of molecular biomarkers related to radioresistance. In conclusion, we discuss biomarkers which are overlapped in most several cancers.